Investigating the Impact of Code-Switching on English Foreign Language Students’ Speaking Confidence - Dewi Kesuma Nasution; Fatimah Sari Siregar (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2021)
Code-switching has attracted many studies in recent years especially in non-native English speaking countries. In some parts of Indonesia, code-switching has been the topic of research. This paper particularly seeks to examine the effect of code-switching on Indonesian Medanese student’s speaking confidence and investigate their attitude towards it. A total of 34 students from English Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Sumatera Utara were chosen purposely to be involved as the participants in the study. An interview and observation were applied to assess their spoken English skill and examine how they interact with each other throughout the sessions. While the ten item questionnaires with a Likert scale were distributed to students to collate their feedback on the implementation of code-switching. It was then explicitly analyzed based on each indicator of speaking, including vocabulary, grammar, fluency, pronunciation and lecturer’s role. Our findings lead to the conclusion and suggest that code-switching can be harnessed as a technique in enhancing students’ speaking confidence since students think positively towards the implementation of code-switching. Hence, based on our findings, it is recommended that lecturers use English and Indonesian at an interchange to lower proficient students so as to give students better comprehension of grammar rules, structure, pronunciation, and subsequently improve their fluency and confidence in speaking.